Introducing the epileptome: Dynamic seizure onset zone connectome as revealed by single pulse electrical stimulation in stereoelectroencephalography. Issue 3 (March 2016) - Maliia, M.D.; Donos, C.; Barborica, A.; Popa, I.; Ciurea, J.; Mindruta, I.
Abstract : Purpose: Design a protocol for probing the plastic nature of the epileptic networks. Methods: We selected 3 patients with pharmaco-resistant epilepsy that were explored in the SEEG method. Single pulse electrical stimulations (SPES) (biphasic, 3 ms, 0.25–5 mA) were applied to adjacent contacts. We calculated the early responses in the 10–110 ms interval and considered only connections between contacts having a RMS value within the 3rd quartile of all the responses in an individual patient, correlated with the stimulation current (Spearman's rho >0.5, p  < 0.05). Sublobar anatomical structures projecting to SOZ (inbound connections), as well as SOZ's projections to other structures (outbound connections) were systematically assessed and named generically "epileptome". SOZ's contacts were also stimulated in various relevant clinical situations (first, second patient-interictal awake vs. sleep vs. postictal, third-on medication vs. off) to understand the dynamics of the outbound analysis. Results: Lack of medication or sleep activated SOZ's network (mean increase in RMS 6%, 28% to baseline) and introduced new structures in the epileptome (hippocampus in one patient, contralateral basal temporal and precuneus in another). Post-seizure, SOZ lost some nearby connections and gained distant ones, not present interictally. Conclusions: Intra-individually the epileptic focus engages in an evolving network configuration that can be accurately described.